Isolation, molecular characterization, and therapeutic evaluation of bacteriophages targeting shiga toxin-producing Escherichia coli (STEC) - DEBBARMA, HILARI; SATPATHY, MOON MOON; SANJANA; ARUN, AMBIKA; ABHISHEK; KUMAR, BABLU (The Indian Journal of Animal Sciences, 2026)
Shiga toxin-producing Escherichia coli (STEC) is an important foodborne pathogen responsible for severe gastrointestinal infections in humans and animals. The present study aimed to isolate and characterize bacteriophages targeting STEC and evaluate their potential for bacterial control. Twenty-two E. coli isolates were revived and confirmed using cultural, biochemical, and molecular methods. Molecular analysis showed that 86.36% of isolates carried the stx1 (Shiga toxin 1) gene and 50% carried the eae (Escherichia coli attaching and effacing) gene, while stx2 was not detected. Thirteen bacteriophages (Ecp1–Ecp13) were isolated from farm environments and hospital sewage, of which twelve exhibited lytic activity against STEC isolates. Five phages showing broader lytic spectra were further characterized. Transmission electron microscopy identified them as members of the order Caudovirales, belonging to the families Podoviridae and Siphoviridae. The phages remained stable across temperatures from −20°C to 37°C and within pH 4–9, with optimal stability at 4°C and pH 7.5 Time-kill analysis demonstrated rapid bacterial reduction by phage Ecp10, and its application in experimentally contaminated milk significantly reduced STEC counts compared to untreated controls. These findings highlight the potential of bacteriophages as natural and targeted biocontrol agents for reducing STEC contamination in food systems.